La représentation de la laïcité dans les manuels scolaires grecs depuis son adhésion à la Communauté européenne (1981-2018) - Eleni Kalesi (Les éditions de la Maison des sciences de l'Homme, 2022)
Since the establishment of the modern Greek state in the 19th century, its educational system conveys a school discourse imbued with the orthodox religion: participation in religion classes, religious celebrations and morning prayer in school are some significant examples. But what happened when Greece joined the European Community in 1981 and is now obliged to comply with eu rules on freedom of religion? The present article deals with this challenge, known as laïcité (secularism), and the means that the Greek education system uses to integrate the concept into its school discourse. It is based on the major components of laïcité to analyze the content of religious, history and civic education school textbooks of primary and secondary education during the last forty years (1981-2018) and then, to observe the possible transformations in the way laïcité is presented.